The Effect of Foot Massage on Diabetic Neuropathy Symptoms in Patients with Diabetes Mellitus at Kabila Health Center - Nur Fadilah Putry Nalole; Zuhriana K. Yusuf; Sitti Fatimah Arsad (Universitas Muhammadiyah Palu, 2026)
Diabetes mellitus is a non-communicable disease with high morbidity and mortality rates that can cause complications of diabetic neuropathy due to chronic hyperglycemia and low physical activity. Diabetic neuropathy causes complaints such as tingling, nausea, pain, and sensory disturbances that decrease quality of life, so non-pharmacological interventions are needed as a safe and effective alternative. Foot massage was chosen as one of the interventions because it is easy to do, low cost, can be applied by patients and families, and has been proven to be effective in reducing symptoms of diabetic neuropathy. The purpose of this research is to determine the effect of Foot Massage on the symptoms of Diabetic Neuropathy in Diabetes Mellitus patients. This study is a quasi-experimental study with a pre-test post-test with control group design involving 18 respondents in the experimental group and 18 respondents in the control group taken using purposive sampling techniques. The results of the study showed that after being given foot massage therapy, the experimental group experienced a decrease in symptoms of diabetic neuropathy, where 27.8% of respondents were in the category of mild symptoms, 66.7% of moderate symptoms, and only 5.6% still experienced severe symptoms. On the other hand, in the control group there was no meaningful change, with the majority of respondents (83.3%) remaining in the moderate symptom category. The results of the Independent t-test showed a significance value of 0.001 (p < 0.05), which proved that foot massage therapy had a significant effect on reducing symptoms of diabetic neuropathy in patients with diabetes mellitus at the Kabila Health Center.